Investigating the Role of Students' Attitudes, System Quality and Knowledge Management in the Behavior of Using E-Learning through the Mediation of E-Learning Acceptance - Mohammad Razzaghi; Aziz Hedayati Khoshmehr; Abolfazl Ghasemzadeh Alishahi; Rahim Shahbazi (علوم و فنون مدیریت اطلاعات, 2023)
Purpose: The aim of this study was to investigate the role of students' attitudes, system quality, and knowledge management in the behavior of using e-learning through the mediation of e-learning acceptance among students of the Farhangian University of Fars Province.Methods: This research is applied in terms of purpose and nature and a descriptive correlation based on structural equation modeling in terms of data collection province in 2021-2022 with a number of 4450 people. According to Krejcie & Morgan's table, 351 people were selected as a sample through the proportional stratified random sampling method. To measure the research variables, the standard questionnaire ofstudents' attitudes towards e-learning, Akbar (2013), researcher-made system quality questionnaire, Sharon Lawson's standard knowledge management questionnaire (2003), researcher-made e-learning acceptance questionnaire, and the standard questionnaire of the actual use of the e-learning system (Akbar, 2013) were used. The validity of the questionnaires was confirmed by content and structure validity methods (confirmatory factor analysis) and respectively, the reliability by Cronbach's alpha coefficient is 0.89, 0.79, 0.94, 0.82, and 0.86 was estimated and confirmed. Data were analyzed at two levels of descriptive and inferential (structural equations) using SPSS 24 and Lisrel 8.8 software.Findings: The results indicate that among the variables of Students' Attitudes with acceptance of e-learning (β=0.52), System quality with acceptance of e-learning (β=0.89), knowledge management with acceptance of e-learning (β=0.67) and acceptance of e-learning with real use of the system (β=0.17) There is a positive and significant causal relationship. Students' Attitudes, System quality, and knowledge management mediate e-learning acceptance and indirectly affect the actual use of the e-learning system. Therefore, the mediating effect of e-learning acceptance in this study was confirmed.Conclusions: According to the findings of this study, it can be seen that an increase in students 'attitudes, system quality, knowledge management, and acceptance of e-learning scores will be associated with an increase in students' e-learning usage behavior. According to the research findings, policymakers and university administrators are suggested to prepare the ground for real use and acceptance of e-learning in the learning process of Farhangian University by holding workshops and training courses while paying attention to the variables of the present research.